Avaliação da resistência à corrosão de chapas espessas de aço inoxidável lean duplex UNS S32304 soldadas pelos processos SMAW, GMAW e FCAW em meio corrosivo da indústria de biodiesel - Dalila Chaves Sicupira (2015)
UNS S32304 Lean Duplex Stainless Steel (LDSS) thick plates were welded by different processes commonly employed in the manufacture of equipment and piping: shielded metal arc welding (SMAW), gas metal arc welding (GMAW) and flux cored arc welding (FCAW). The electrochemical behavior of different weldment zones (fusion zone (FZ), base metal (BM) and heat affected zone (HAZ)) was characterized both independently, using an electrochemical microcell, and together by testing the whole welded area. The electrochemical tests were performed in acidified glycerin, a byproduct of the biodiesel industry. The study of the corrosion behavior of the welded joints was performed using electrochemical techniques such as cyclic potentiodynamic polarization, electrochemical impedance spectroscopy and Mott-Schottky analysis. Optical microscopy, transmission electron microscopy and scanning electron microscopy were used for sample characterization. The results were correlated to the microstructural features of the materials. The capacitance study showed that the passive films formed on welded LDSS behaved as n-type and p-type semiconductors above and below the flat band potential, respectively. Furthermore, the samples welded by the Gas Metal Arc Welding process exhibited better corrosion resistance than others welding processes using the same filler metal. Results for pitting potential using microcell technique and SEM images showed that the HAZ was the most critical zone for pitting corrosion for all samples. No chromium nitride precipitation was observed in the specimens without welding, while many nitride precipitates were found at grain boundaries or ferrite grains in the welded specimens. These pits are believed to be closely related with the Cr2N precipitates. In general, the corrosion resistance of the top regions of welds was higher in acidified glycerin than that of weld roots. Basically, all xiii the welded samples exhibited similar or a higher corrosion resistance, compared with the corresponding base metal.